Determination of octanol-water partition coefficients of anti-microbial alkaloids from Glycosmis pentaphylla (Retz) DC - Ahmad, Kausar; Mohd Hassan, Norazian; Helal Uddin, A.B.M.; Mat Ali, Idura; Mansor, Norhafizah (2010)
Octanol-water partition coefficient (KOW) values of anti-microbial alkaloids, arborine and arborinine of Glycosmis pentaphylla (Retz) DC were determined. The method of extraction by solvents of these alkaloids and the following isolation procedures using column chromatography techniques will adopt those ascertained and established earlier (Norazian, 2006). A shake-flask method was used to determine the octanol-water partition coefficients from (298.15, 303.15, 308.15 and 313.15)k. Each compound was dissolved in the octanol to a known concentration and placed in octanol-water system and allowed to equilibrate. The concentration in the octanol phase was then determined by using spectrophotometer. The KOW was calculated as the ratio of the concentration in octanol phase to the concentration in aqueous phase.